Neuropsychiatric symptoms related to cholinergic deficits in Parkinson’s disease - Pérez Lloret, Santiago (2017)
Fil: Pérez Lloret, Santiago. Universidad de Buenos Aires. Facultad de Medicina. Instituto de Investigaciones Cardiológicas; Argentina